English Language Imperative Level in Indonesia - Dedi Rahman Nur; Jamilah Jamilah (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2022)
In general, a language is a tool for communication that every people use, and as we know there are many languages especially in Indonesia. It is a regional or local language that people use for their daily activities with their family or with their local people, Indonesian language is an official language that people use on, the daily activities in formal places or with work partners. Indonesia's government has already made some regular or policy to manage language use also the regulation about English as a foreign language. But the use of the English language is not optimal especially in the world of education even though English has become the lingua franca in the world. For such a stance, the writer has no goal to blame any culture nor suggests that English culture is not meant to be learned. The writer concerns more with the idea that in learning English, the culture of learners is more urgent than English culture since the use of English is around peer communication. The awareness of English as an International language and as a language of science is responded with mandatory English teaching in Junior High school to the varsity level. However, with the status as a foreign language, English is occasionally used outside the classroom. Even during the class, instead of speaking English, the Indonesian students tend to speak in Bahasa Indonesia (Indonesian Language) or their local language. For that, the writer gives some proposed solutions after analyzing some literature, The writer used the Systematic Literature Review framework from (Okoli, 2015) to perform this review of the literature